2022
DOI: 10.1136/bmjopen-2022-063426
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of quality of antenatal care and associated factors among pregnant women in Ethiopia: a community based cross-sectional study

Abstract: ObjectiveTo determine the magnitude of quality of antenatal care and associated factors among pregnant women in Ethiopia.DesignA community-based cross-sectional study.SettingEthiopia.ParticipantsA total of 4757 weighted sample of pregnant women from 18 January 2016 to 27 June 2016, were included for this analysis.OutcomeQuality of antenatal care (ANC).MethodsOur analysis was based on secondary data using the 2016 Ethiopian Demographic and Health Survey. The quality of ANC was measured when all six essential co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 58 publications
5
15
0
Order By: Relevance
“…Model III was the best-fitted model since it had the lowest deviance. Variables having a p-value less than 0.2 in bivariable analysis were used for multivariable analysis [ 49 51 ]. Finally, in the multivariable analysis, adjusted odds ratios with 95% confidence intervals and a p-value of less than 0.05 were used to identify factors of SBI.…”
Section: Methodsmentioning
confidence: 99%
“…Model III was the best-fitted model since it had the lowest deviance. Variables having a p-value less than 0.2 in bivariable analysis were used for multivariable analysis [ 49 51 ]. Finally, in the multivariable analysis, adjusted odds ratios with 95% confidence intervals and a p-value of less than 0.05 were used to identify factors of SBI.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas studies in other African countries like South Africa [13], Tanzania [48], and Nigeria [11] revealed that the prompt attention domain was poorly performed. Te concern for these domains might be due to factors such as overcrowding, understafng, delays in reception, inaccessibility to recommended medicines, provider attitudes, and poor healthcare management that could probably contribute to low responsiveness [11,49].…”
Section: Responsiveness Performancementioning
confidence: 99%
“…The new approach to ANC emphasizes the quality of care rather than quantity [4]. However, Evidences suggested that, not more than one third of the pregnant women receive a good quality ANC service [5][6][7]. Studies have shown that there are many missed opportunities for care, both because of the client-and health system-related factors.…”
Section: Introductionmentioning
confidence: 99%